2021
DOI: 10.1007/978-3-030-76559-0
|View full text |Cite
|
Sign up to set email alerts
|

Multi-UAS Minimum Time Search in Dynamic and Uncertain Environments

Abstract: La tesis es una obra original que no infringe los derechos de propiedad intelectual ni los derechos de propiedad industrial u otros, de acuerdo con el ordenamiento jurídico vigente, en particular, la Ley de Propiedad Intelectual (R.D. legislativo 1/1996, de 12 de abril, por el que se aprueba el texto refundido de la Ley de Propiedad Intelectual, modificado por la Ley 2/2019, de 1 de marzo, regularizando, aclarando y armonizando las disposiciones legales vigentes sobre la materia), en particular, las disposicio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 83 publications
(346 reference statements)
0
2
0
Order By: Relevance
“…In formula (17), R m represents the mass of the UAV, and the force of the UAV in each axial direction is composed of two parts, where…”
Section: Small Uav System Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In formula (17), R m represents the mass of the UAV, and the force of the UAV in each axial direction is composed of two parts, where…”
Section: Small Uav System Modelmentioning
confidence: 99%
“…Many researchers have been looking into the problem of cooperative path planning of multiple UAVs [12][13][14]. More research on drones can be found in [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%